1988
DOI: 10.1212/wnl.38.5.806
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit disorder in children

Abstract: This study tests the hypothesis that children with attention deficit disorder (ADD) resemble adults with inattention and neglect secondary to right hemisphere dysfunction. A letter cancellation task was administered to seven boys with ADD and five controls. As a group, the subjects with ADD made significantly more overall errors of omission and left-sided errors than controls, suggesting that they resemble adults with right hemisphere dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 0 publications
9
70
2
Order By: Relevance
“…The asymmetry of human spatial attention is well documented in both disease and healthy states: right-hemisphere (RH) lesions are more frequently associated with hemispatial neglect compared with left-hemisphere (LH) lesions and usually cause more severe and persistent deficits (Mesulam, 1999); moreover, a leftward bias in the perception of length, size, brightness, and numerosity, termed right "pseudoneglect," is frequently reported in healthy subjects (Orr and Nicholls, 2005); and finally, left-rather than right-sided inattention has been reported in patients with attention deficit disorder (ADD) (Voeller and Heilman, 1988) and developmental dyslexia (Hari et al, 2001;Sireteanu et al, 2005). A recent report of a leftward attention bias in birds (Diekamp et al, 2005) suggests a fundamental evolutionary role for this bias.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetry of human spatial attention is well documented in both disease and healthy states: right-hemisphere (RH) lesions are more frequently associated with hemispatial neglect compared with left-hemisphere (LH) lesions and usually cause more severe and persistent deficits (Mesulam, 1999); moreover, a leftward bias in the perception of length, size, brightness, and numerosity, termed right "pseudoneglect," is frequently reported in healthy subjects (Orr and Nicholls, 2005); and finally, left-rather than right-sided inattention has been reported in patients with attention deficit disorder (ADD) (Voeller and Heilman, 1988) and developmental dyslexia (Hari et al, 2001;Sireteanu et al, 2005). A recent report of a leftward attention bias in birds (Diekamp et al, 2005) suggests a fundamental evolutionary role for this bias.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the presence of attentional asymmetries in ADHD using both clinical and experimental measures of attention (Voeller and Heilman, 1988;Carter et al, 1995;Nigg et al, 1997;McDonald et al, 1999;Sheppard et al, 1999). Failure to replicate these effects in some studies (Wood et al, 1999;Klimkeit et al, 2003), nevertheless, suggests neuropsychological heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Results of many investigations suggest that the problems in ADHD may be due to a lateralised disturbance in the frontal lobe network function, mediated by the under activity of predominantly the right hemispheric frontostriatal regions (9,32,33,34). Functional neuroimaging studies, using single photon emission computed thomography (SPECT), positron emission thomography (PET) and functional magnetic resonance imaging (fMRI) have identified anomalies of frontal metabolic activity indexed by diminished cerebral blood flow or glucose metabolism (5,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown an association between the diagnosis of childhood ADHD and a relative reduction in awareness for visual information presented on the left (6,7,8,9). Normally, visual stimuli evoke predominantly right hemisphere activity, so that attention is directed preferentially to the left.…”
mentioning
confidence: 99%